Numerical Simulation of Thermo-Hydro-Mechanical Coupling of Model Test for Nuclear Waste Disposal - Yu-Ping Wang; Zhe Wang; Fa-Cheng Yi; Lei Fu; Ying Luo (Applied Sciences)
This article presents a simulation of a long-term retardation performance Mock-up test of the multi-field coupling of buffer materials, with the aim to study the thermo-hydro-mechanical (THM) processes occurring in the engineered barrier system of a high-level waste (HLW) repository. In view of the theory of mixtures and mechanics of continuous media, the coupled THM mathematical model of unsaturated buffer materials is established, considering heat transport and multiphase fluid flow. Using the buffer material Mock-up test of multi-field coupling as a model, the partial differential equation (PDE) module in the general finite element software COMSOL Multiphysics was developed by a second development stage. The dynamic response process of buffer material under the condition of THM coupling was numerically simulated, and the spatial distribution and variation law of suction, porosity, horizontal displacement, temperature and swelling pressure in the engineered barrier were investigated. The porosity of the buffer material under THM coupling was influenced by the swelling pressure and the suction. The welling pressure evolution of the buffer material may be influenced by the thermal expansion induced by high temperature and the swelling pressure generated by buffer material saturation. The evolution of the horizontal displacement of the heater used to simulate a container with radioactive waste was validated. This paper provides technical reference for the design and safety evaluation of underground laboratory barrier engineering in China.